Peningkatan Pembelajaran Mata Pelajaran Melalui Kursus Bimbingan Belajar Gratis di SDN 03 Rantau Selatan - Monalisa Marta Siahaan; Rebika Afrina Br Simanjuntak; Mia Agustine Carolina Sianturi; Inka Wulansari Manik; Efriana Pangaribuan; Jesica Sandrina Lumbantobing; Marrejeki Siahaan (Utan Kayu Publishing, 2022)
The purpose of implementing community service (PkM) is to establish professional teachers/educational staff through training activities at partner schools. Learning activities are carried out using tools including smartphones and laptops. and using applications including through WhatsApp (WA), and learning outside of school held at the Command Post as a medium for increasing knowledge. Community Service Program (PkM) activities are carried out at the SMP Negeri 2 Rantau Selatan for 1 month starting from February 2, 2022 to February 26, 2022. Good communication, coordination, and cooperation are the main keys to the smooth implementation of PkM activities. The result of this PkM implementation is that students at the school become more helpful and also make it easier for them to repeat every material that has been studied at school and repeated in additional lessons held in PkM. The hope is that the school can also continue to facilitate any additional lessons for students that are useful for them to improve their learning of each subject at school.